Kinematic Detections of Protoplanets: A Doppler Flip in the Disk of Hd 100546 - Perez-Marquez, S (Institute of Physics Publishing, 2019)
Protoplanets and circumplanetary disks are rather elusive in their thermal IR emission. Yet they are cornerstones to the most popular interpretations for the protoplanetary disk structures observed in the gas and dust density fields, even though alternative theories exist. The gaseous velocity field should also bear the imprint of planet-disk interactions, with non-Keplerian fine structure in the molecular-line channel maps. Such kinks or wiggles are affected by the optical depth structure and synthesis imaging limitations, but their detail could in principle be connected to the perturber by comparison with hydrodynamical simulations. These predictions appear to have been observed in HD 163296 and HD 97048, where the most conspicuous wiggles are interpreted in terms of embedded planets. The velocity centroid maps may allow for more robust indirect detections of embedded planets. The non-Keplerian velocity along the planetary wakes undergoes an abrupt sign reversal across the protoplanet. After subtraction of the disk rotation curve, the location of the perturber should be identifiable as a Doppler flip in velocity centroid maps. Here we improve our rotation curves in an extension to disks with intermediate inclinations, which we apply to deep and fine angular resolution CO isotopologue data sets. Trials in HD 163296 and in HD 97048 yield nondetections. However, in HD 100546 we pick up a conspicuous Doppler flip, an important part of which is likely due to radial flows. Its coincidence with a fine ridge crossing an annular groove inside the continuum ring suggests a complex dynamical scenario, in which the putative protoplanet might have recently undergone pebble accretion. © 2019. The American Astronomical Society. All rights reserved..